Engaging stakeholders to develop nascent entrepreneurial ecosystems in Brazil - Yamaçake, Franklin Thiago Ribeiro (2024)
Entrepreneurial ecosystems serve as a catalyst for fostering high-growth entrepreneurial activities, yet a clear understanding of how to effectively engage stakeholders in their development remains elusive to both ecosystem leaders and academics. This study seeks to enrich the theoretical discourse by integrating perspectives from entrepreneurial ecosystems, stakeholder engagement, and Self-Determination Theory. Spanning three consecutive and interconnected studies, the methodology employed in this thesis is multifaceted. The initial study conducted a systematic literature review to distill prevalent recommendations from scholarly discourse on entrepreneurial ecosystem development. Building upon this foundation, the second study delved into a singular case study within the emergent entrepreneurial ecosystem of Jundiaí, known as Grape Valley. Here, the focus was on scrutinizing the factors that motivate stakeholders to actively participate in advancing the entrepreneurial ecosystem, with a lens grounded in Self-Determination Theory. The third study builds on these insights by investigating the impact of Relatedness, Competence, Autonomy, and Purpose on stakeholder engagement within the broader entrepreneurial ecosystem domain. The findings arising from the triad of investigations are as follows: A total of 74 recommendations emerged, covering dimensions such as Policy, Support, Culture, Human Capital, Market, and Finance in the development of entrepreneurial ecosystems. The second study identified 35 factors influencing stakeholders' active engagement in nascent entrepreneurial ecosystems, revealing a new basic psychological need termed Purpose. The third study highlighted that, among basic psychological needs, Competence and Relatedness significantly influence stakeholder engagement, whereas Autonomy showed no discernible effect. The emergence of Purpose as a critical factor signals the need for more in-depth exploration. In terms of originality and value, this study makes significant theoretical contributions by seamlessly merging Self-Determination Theory with stakeholder engagement in the context of entrepreneurial ecosystems. Additionally, it advocates for the inclusion of Purpose as a pivotal element for understanding stakeholder engagement dynamics, thereby expanding the conceptual boundaries of existing frameworks.